Knowledge Management sebagai Strategi Peningkatan Kinerja Organisasi Pendidikan di Era Transformasi Digital: Systematic Literature Review - Ellyantika Sari; Eklianti Eklianti; Rahayu Arna Vidya; Tjhia Khie Khiong (Indo Publishing, 2026)
This study aims to analyze the implementation of Knowledge Management (KM) as a strategy to improve educational organizational performance in the era of digital transformation through a Systematic Literature Review (SLR). A total of 51 scholarly articles were selected using the PRISMA guidelines and analyzed through thematic analysis. The findings reveal five key dimensions influencing KM implementation: digital maturity, knowledge-sharing effectiveness, institutional performance improvement, digital literacy capability, and sustainable technological infrastructure. The integration of digital technology, knowledge-sharing culture, human resource development, and digital leadership significantly enhances operational efficiency, innovation, and educational service quality. This study concludes that the synergy of technology, people, and organizational culture is essential for successful KM implementation and sustainable digital transformation in educational institutions.